PENINGKATAN PENGGUNAAN FINANCIAL TECHNOLOGI MELALUI FINANCIAL LITERACY PADA GENERASI Z DI ERA SOCIETY 5.0 - Roy Rocky Suprapto Baan; Pierdijono Hartono; Veronika Yuni; Siti Hasanah; Kraugusteeliana Kraugusteeliana (ITB AAS Indonesia Surakarta, 2024)
In the current era of globalization, technological advances have become a new driver for economic growth, especially in the financial sector, where fintech has been able to become a new instrument to encourage growth in this sector. This research aims to find out whether there is an influence between financial literacy and the increased use of financial technology (fintech) in generation z in the era of society 5.0. The research method used is a quantitative method. The data used in this research is primary data where the data is obtained directly from respondents' answers to questionnaires distributed to generation z in Bandar Lampung City. The respondents of this research are generation z in Bandar Lampung City who were born in 1997-2005. Data analysis techniques use software Smart PLS vers 3.. The results of this research are that financial literacy has a positive and significant influence on the use of financial technology in generation z in the city of Bandar Lampung.